MXene / chitosan / glutaraldehyde porous material as well as preparation method and application thereof

By using MXene/chitosan/glutaraldehyde porous materials as the evaporation structure of solar evaporators, the problems of low heat transfer efficiency and non-degradable materials in the prior art are solved, and efficient seawater desalination and sewage purification are achieved, and environmentally friendly.

CN119775628APending Publication Date: 2025-04-08ZHENGZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510084976.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Existing solar evaporators have shortcomings in heat transfer and material degradability, resulting in energy waste and environmental pollution.

Method used

The MXene/chitosan/glutaraldehyde porous material is used as the evaporation structure, and the low-temperature directional ice crystal growth and glutaraldehyde cross-linking technology are used to form a material with excellent photothermal conversion and good mechanical properties.

Benefits of technology

It realizes efficient photothermal conversion, reduces evaporation enthalpy and thermal conductivity, avoids heat waste and precipitation of salt crystals, ensures long-term stable operation, and the material is degradable and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775628A_ABST
    Figure CN119775628A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of photo-thermal materials, and discloses an MXene / chitosan / glutaraldehyde porous material as well as a preparation method and application thereof. The preparation method comprises the following steps: (1) pre-cooling an MXene / chitosan homogeneous dispersion liquid, then putting the pre-cooled MXene / chitosan homogeneous dispersion liquid into a coolant for directional ice crystal growth to obtain an MXene / chitosan frozen sample, and freeze-drying the MXene / chitosan frozen sample to obtain an MXene / chitosan porous material; and (2) adding the MXene / chitosan porous material into a glutaraldehyde aqueous solution for full infiltration, then taking out and absorbing dry, putting into water for immersion cleaning and absorbing dry, and finally airing to obtain the MXene / chitosan / glutaraldehyde porous material. According to the MXene / chitosan / glutaraldehyde porous material prepared by the infiltration method, an aldehyde group of glutaraldehyde reacts with an amino group of chitosan to form a carbon-nitrogen double bond, so that the physical properties of a chitosan skeleton in a wet state are improved. The solar evaporator prepared from the MXene / chitosan / glutaraldehyde porous material has excellent photo-thermal conversion performance, high evaporation efficiency and high desalination and purification efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photothermal materials and discloses a MXene / chitosan / glutaraldehyde porous material and a preparation method and application thereof. Background Art

[0002] Ensuring an adequate and stable supply of fresh water is essential for human survival and economic productivity. However, challenges such as unreasonable agricultural irrigation methods, uneven water distribution, and pollution of fresh water sources have significantly affected the availability of fresh water. Desalination technology has become an important way to solve the problem of water shortage. Solar energy, as an abundant and clean energy source, can effectively remove salt from water by using solar energy to heat water to generate water vapor and then condense it to obtain fresh water. It is the most economical and sustainable way to achieve this goal.

[0003] Based on this, solar evaporators have been widely developed in recent years. Compared with traditional desalination methods, solar evaporators have the advantages of fast evaporation rate, high evaporation efficiency, low production cost, and no need for additional energy supply. Solar evaporators with directional structures have the advantages of low evaporation enthalpy and strong water supply capacity. However, most of the longitudinal directional structures currently used also enhance the heat transfer from the evaporation surface to the water body, resulting in energy waste. And most of the evaporators currently use non-woven fabrics, foams and other materials made of non-degradable polymers as matrix materials. Although these materials have excellent performance and low cost, they will cause pollution to the natural environment when they fail and are discarded. Therefore, it is necessary to provide a matrix material for an environmentally friendly solar evaporator. Summary of the invention

[0004] In view of the problems and shortcomings in the prior art, the present invention aims to provide a MXene / chitosan porous material and a preparation method and application thereof.

[0005] In order to achieve the purpose of the present invention, the technical solution adopted by the present invention is as follows:

[0006] The first part of the present invention provides a method for preparing a MXene / chitosan / glutaraldehyde porous material, comprising the following steps:

[0007] (1) precooling a MXene / chitosan homogeneous dispersion, placing the precooled dispersion in a coolant for directional ice crystal growth, obtaining a MXene / chitosan frozen sample, and freeze-drying to obtain a MXene / chitosan porous material;

[0008] (2) adding the MXene / chitosan porous material prepared in step (1) into the glutaraldehyde aqueous solution, allowing the MXene / chitosan porous material to stand until the MXene / chitosan porous material is fully soaked, then taking it out and absorbing it, immersing it in water, absorbing it and finally drying it to obtain the MXene / chitosan / glutaraldehyde porous material.

[0009] Preferably, the mass fraction of glutaraldehyde in the glutaraldehyde aqueous solution in step (2) is 40wt% to 60wt%.

[0010] Preferably, the MXene / chitosan homogeneous dispersion in step (1) is prepared by adding chitosan powder to a MXene dispersion, dissolving the powder, and ultrasonically defoaming the dispersion, and the concentration of chitosan in the MXene / chitosan homogeneous dispersion is 20 to 30 mg / mL.

[0011] More preferably, the ultrasonic treatment time is 1 to 2 hours.

[0012] More preferably, the MXene dispersion is prepared by uniformly dispersing MXene powder in an acetic acid aqueous solution, the concentration of MXene in the MXene dispersion is 4 mg / mL, and the volume fraction of acetic acid in the acetic acid aqueous solution is 2%.

[0013] More preferably, the MXene is Ti3C2, Ti3C2T x 、Ti2CT x 、Nb2CT x wherein T is one of -OH, -Cl, and -F, and x is the number of T.

[0014] More preferably, the MXene is Ti3C2.

[0015] Preferably, the precooling time in step (1) is 0.5 to 1 h, and the precooling temperature is -5 to 5°C.

[0016] Preferably, the coolant in step (1) is -40°C ethanol, and the ice crystal growth time is 10 to 15 minutes.

[0017] Preferably, the freeze-drying conditions in step (1) are: temperature of -50°C, air pressure less than 100 Pa, and time of 72 hours.

[0018] Preferably, in step (2), the porous material is immersed in water for 6 to 10 times.

[0019] The second part of the present invention provides a MXene / chitosan / glutaraldehyde porous material prepared by the method described in the first part above.

[0020] The third part of the present invention provides an application of the MXene / chitosan / glutaraldehyde porous material described in the second part in the preparation of a solar evaporator.

[0021] Preferably, the solar evaporator comprises an evaporation structure and a support structure, wherein the evaporation structure is made of MXene / chitosan / glutaraldehyde porous material.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] (1) The present invention adopts an infiltration method to prepare MXene / chitosan / glutaraldehyde porous materials. The aldehyde group of the introduced glutaraldehyde reacts with the amino group of chitosan to form a carbon-nitrogen double bond, and finally forms a Schiff base cross-linked network, which greatly improves the physical properties of the chitosan skeleton in a wet state. MXene / chitosan uses degradable chitosan as the material skeleton, and MXene as a light absorber is evenly embedded in the chitosan skeleton and is not easy to fall off. The present invention adopts an integrated molding method to evenly fix MXene on the porous material skeleton, so that the amount of MXene used is less, which effectively reduces the cost and consumption of raw materials, and the preparation method is simple and easy to scale production.

[0024] (2) The present invention adopts a method of low-temperature directional ice crystal growth to prepare a MXene / chitosan porous material, wherein MXene is dispersed in an acetic acid aqueous solution to form a MXene dispersion, deionized water is used as a solvent, and acetic acid is used as a pH regulator. Since deionized water has a good dispersibility for MXene, and chitosan can only be dissolved in an acidic environment, the addition of acetic acid can dissolve chitosan in the MXene dispersion. When the MXene / chitosan dispersion is in a coolant, due to the temperature difference between the test tube wall and the center, ice crystals grow from the outside to the inside toward the center, forming a radial structure.

[0025] (3) The solar evaporator prepared by the present invention uses MXene / chitosan / glutaraldehyde porous material as the evaporation structure, has excellent light-to-heat conversion performance, can absorb solar energy and convert it into heat energy, heat the water on the evaporation surface to produce water vapor, and can achieve a high evaporation rate. At the same time, the layered radial channels inside it can continuously transport water to the evaporation interface through capillary action, effectively reducing the evaporation enthalpy while also reducing the thermal conductivity of the evaporation structure, effectively preventing heat from being lost from the evaporation interface to the water body. The salt concentration gradient difference between the evaporation surface and the water body is formed by the evaporation of water, and the salt ions are transferred from the high concentration (evaporation surface) to the low concentration (seawater in the lower layer) and transported back to the water body below, thereby avoiding the problem of surface salt crystal precipitation and the reduction of evaporation efficiency of traditional solar evaporators during long-term operation, and can operate stably for a long time. Using PS foam as a supporting structure can effectively make the evaporation structure float on the water body, avoiding the evaporator from being immersed in the water body to cause heat loss, thereby achieving efficient seawater desalination and sewage purification. At the same time, the preparation material chitosan of the present invention can be completely degraded, and MXene will not be completely degraded, but it is harmless to the environment, so it will not cause environmental pollution, is very friendly to the environment, and achieves the goal of sustainable development.

[0026] (4) The solar evaporator prepared by the present invention is subjected to simulated sunlight (1 kW m -2) can reach 2.47kg m -2 h -2 At the same time, the solar evaporator of the present invention has a good removal effect on salt ions in seawater and dyes in sewage, and has a good effect on K + , Ca 2+ 、Na + Mg 2+ The ion removal efficiency is as high as 99.9%, which can almost completely remove the simulated dyes methylene blue (MB) and methyl orange (MO) in water. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 These are SEM images of porous materials prepared in Examples 1 and 2 of the present invention, wherein (a) and (b) are cross-sectional and longitudinal sections of the MXene / chitosan porous material before glutaraldehyde modification in Example 1, and (c) and (d) are cross-sectional and longitudinal sections of the MXene / chitosan / glutaraldehyde porous material after glutaraldehyde modification in Example 2;

[0028] Figure 2 Compression test diagram of MXene / chitosan porous materials and MXene / chitosan / glutaraldehyde porous materials prepared in Example 1 and Example 2 of the present invention in a wet state;

[0029] Figure 3 This is a water contact angle test diagram of the MXene / chitosan / glutaraldehyde porous material prepared in Example 2 of the present invention, where (a) is the contact angle when the water drop is just added, and (b) is the contact angle when the water drop is completely absorbed;

[0030] Figure 4 UV-visible-infrared absorption curves (above) and AM1.5 solar energy density spectra (below) of the MXene / chitosan porous materials and MXene / chitosan / glutaraldehyde porous materials prepared in Examples 1 and 2 of the present invention;

[0031] Figure 5 This is a DSC test graph of the MXene / chitosan / glutaraldehyde porous material and water prepared in Example 2 of the present invention;

[0032] Figure 6 This is a schematic diagram of the structure of a solar evaporator prepared in Example 3 of the present invention;

[0033] Figure 7 The solar evaporator prepared in Example 3 of the present invention is 1kW / m 2 Evaporation rate curve under light intensity;

[0034] Figure 8 K before and after the solar evaporator prepared in Example 3 of the present invention purifies real seawater+ , Ca 2+ 、Na + Mg 2+ Ion concentration comparison chart;

[0035] Fig. 9 Absorbance curves of the solar evaporator prepared in Example 3 of the present invention before and after purification of methyl orange (MO) and methylene blue (MB) simulated dye wastewater. DETAILED DESCRIPTION

[0036] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below through embodiments in combination with the accompanying drawings. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0037] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0038] Example 1 Preparation of MXene / chitosan porous material

[0039] This embodiment provides a method for preparing a MXene / chitosan porous material, comprising the following steps:

[0040] (1) 0.2 g of Ti2C3 powder was added to 50 mL of acetic acid aqueous solution composed of deionized water and acetic acid in a volume ratio of 49:1, and ultrasonicated for 1 h using a cell crusher to obtain a 4 mg / mL MXene dispersion;

[0041] (2) adding 1.2 g of chitosan powder (CS) to the MXene dispersion obtained in step (1), stirring at room temperature until completely dissolved, to obtain a MXene / CS homogeneous dispersion, wherein the concentration of chitosan is 24 mg / mL;

[0042] (3) The MXene / CS homogeneous dispersion obtained in step (2) is transferred to a mold and precooled at 0°C for 1 h to obtain a precooled dispersion; the precooled dispersion and the mold are then placed in anhydrous ethanol at -40°C for directional ice crystal growth to obtain a MXene / CS frozen sample with completed ice crystal growth;

[0043] (4) The MXene / CS frozen sample obtained in step (3) was placed in a freeze dryer for freeze drying. The freeze drying conditions were: cold trap temperature -50°C, vacuum degree less than 100 Pa, and after 3 days, the sample was removed from the mold to obtain a MXene / CS porous material.

[0044] The mold used in step (3) is a flat-bottomed glass test tube with an inner diameter of 1.8 cm and a height of 20 cm. The size of the mold can be adjusted accordingly according to actual conditions.

[0045] Example 2 Preparation of MXene / chitosan / glutaraldehyde porous material

[0046] This embodiment provides a method for preparing a MXene / chitosan / glutaraldehyde porous material, and the specific process is as follows:

[0047] The MXene / CS porous material prepared in Example 1 was added to a 50wt% glutaraldehyde aqueous solution (GA) for infiltration. After the MXene / chitosan porous material was completely wetted, it was taken out and dried, and then added to deionized water for 6 to 10 times until the glutaraldehyde was completely washed away, and then placed in a cool and ventilated place to dry to obtain a MXene / CS / GA porous material. After the deionized water immersion, the water needs to be taken out and dried before the next immersion.

[0048] Characterization and performance testing of porous materials:

[0049] (1) SEM characterization

[0050] The chitosan porous materials prepared in Example 1 and Example 2 were subjected to SEM scanning electron microscope testing, and the results are as follows: Figure 1 The SEM results of the cross-sectional and longitudinal microstructures of the MXene / CS porous material prepared in Example 1 are shown in Figure 1 (a) and Figure 1 As shown in (b), it can be seen from the figure that the MXene / CS porous material prepared in Example 1 has a radial structure radiating from the center to the surroundings, with an obvious layered structure in the longitudinal direction, and the channel size is 51 to 109 μm. The MXene / CS porous material has a multi-layer radial oriented structure that can meet the mechanical properties of use; the oriented channel structure has capillary force that is beneficial to the transmission of water, and the good hydrophilicity and smaller channel diameter can effectively reduce the water evaporation enthalpy of the evaporator and improve the evaporation performance. The SEM results of the cross-sectional and longitudinal microscopic morphology of the MXene / CS / GA porous material prepared in Example 2 are shown in Figure 2. Figure 1 (c) and Figure 1 As shown in (d), it can be seen from the figure that compared with the unmodified MXene / CS porous material, the structure of the MXene / CS / GA porous material is basically maintained after glutaraldehyde cross-linking.

[0051] (2) Mechanical properties test

[0052] The chitosan porous materials prepared in Example 1 and Example 2 were subjected to compression tests. The results are as follows: Figure 2As shown, the compression test curve of the MXene / CS porous material prepared in Example 1 is as follows Figure 2 As shown by the red line, the mechanical properties of MXene / CS porous materials in the wet state are low, and the stress at 60% strain is only 1.4 KPa. Therefore, it is necessary to cross-link and modify it to enhance the mechanical properties in order to facilitate the preparation and use of solar evaporators. Figure 2 The green line is the compression test curve of MXene / CS / GA porous material. After glutaraldehyde cross-linking, the mechanical properties of MXene / CS / GA porous material are good. The stress at 60% strain is 190.2KPa, which is increased by two orders of magnitude.

[0053] (3) Contact angle test

[0054] The contact angle test of the MXene / CS / GA porous material prepared in Example 2 was performed, and the results were as follows: Figure 3 As shown, it only takes 1 second for the porous material to completely absorb the water droplets, and the MXene / CS / GA porous material exhibits good hydrophilicity and transport properties.

[0055] (4) Light absorption performance test

[0056] The light absorption properties of the MXene / CS porous material prepared in Example 1 and the MXene / CS / GA porous material prepared in Example 2 were tested using a UV-vis-IR spectrophotometer. The results are as follows: Figure 4 As shown in the figure, MXene / CS porous material (shown by the blue line) and MXene / CS / GA porous material (shown by the red line) have high light absorption capacity in the entire solar radiation wavelength range (300-2500nm), and the solar energy utilization rate of MXene / CS porous material is 92.22%. After cross-linking, the photothermal performance is improved, and the solar energy utilization rate of MXene / CS / GA porous material is 93.87%. The photothermal conversion performance of the solar evaporator is closely related to its solar energy utilization rate. High solar energy utilization rate is the basic condition for achieving efficient solar water evaporation.

[0057] (5) Thermal performance test

[0058] The thermal conductivity and evaporation enthalpy of the MXene / CS / GA porous material prepared in Example 2 and water are shown in Table 1. The thermal conductivity of the MXene / CS / GA porous material is 0.1812 W·m -1 ·K -1 , which is much lower than the 0.5990 W m of water. -1 K -1, low thermal conductivity helps to avoid heat loss to the water body and cause waste. Low evaporation enthalpy helps to reduce the energy required for water evaporation and improve evaporation efficiency. The evaporation enthalpy of MXene / CS / GA porous material is 1573 J / g, which is lower than 2269 J / g of water. The thermal conductivity and water evaporation enthalpy of the solar evaporator have a great influence on its energy utilization efficiency. The DSC curve of the MXene / CS / GA porous material prepared in Example 2 and water is shown in Figure 5 , the energy required for evaporation of MXene / CS / GA porous materials is lower than that of pure water.

[0059] Table 1 Properties of MXene / CS / GA porous materials and water

[0060] Sample No. <![CDATA[Thermal conductivity (W·m -1 ·K -1 )]]> Enthalpy of evaporation (J / g) water 0.5990 2269 Example 2 0.1812 1573

[0061] Example 3 Preparation of solar evaporator

[0062] This example provides a solar evaporator, which includes an evaporation structure and a support structure, such as Figure 6 As shown, the evaporation structure is the MXene / CS / GA porous material prepared in Example 2, and the material of the support structure is polystyrene foam (PS foam). The evaporation structure is embedded in the support structure, and there is a through circular hole in the middle of the support structure for embedding the evaporation structure, and the two together constitute a solar evaporator.

[0063] Performance test of solar evaporator:

[0064] Under the irradiation of a solar simulator, a water evaporation experiment was carried out using the solar evaporator prepared in Example 3, and evaporated condensed water was collected to test the evaporation rate, desalination and purification efficiency of the solar evaporator.

[0065] (1) Evaporation rate test: at 1kW / m 2 Under simulated sunlight, the evaporation rate of the solar evaporator was tested using seawater from the Bohai Sea. The test results are as follows: Figure 7 As shown. Figure 7 It can be seen that the evaporation rate of the new solar evaporator is 2.468 kg·m -2 ·h -1 After the evaporator was immersed in seawater for 3 months, the evaporation rate of the evaporator was 2.426 kg·m -2 ·h -1 , indicating that the evaporator has good long-term performance.

[0066] (2) Desalination efficiency test: The desalination performance of the solar evaporator was investigated using seawater from the Bohai Sea at 1 kW / m 2The water was evaporated under light and the purified condensed water was collected. The K in the seawater before purification and the purified condensed water was determined by ICP-OES. + , Ca 2+ 、Na + Mg 2+ The concentration of four ions is used to calculate the desalination efficiency to characterize the desalination effect of the evaporator. The desalination efficiency calculation formula is: Desalination efficiency = ion concentration in the condensed water after purification / ion concentration in the seawater before purification. The test results are as follows Figure 8 As shown. Figure 8 It can be seen that compared with seawater, the ion concentration in the condensed water is reduced by 2 to 4 orders of magnitude, and the desalination efficiency is as high as 99.9%, reaching the safe salinity standards for drinking water set by WHO and EPA.

[0067] (3) Purification efficiency test: Methylene blue (MB) and methyl orange (MO) were used as simulated dye pollutants, and a dye solution with a concentration of 20 mg / L was prepared to simulate sewage at 1 kW / m 2 Water was evaporated under the illumination of the solar evaporator to test the purification ability of the dye wastewater. The absorption spectra of the simulated wastewater and the purified condensed water were detected by UV-vis spectrophotometer to characterize the purification effect. The results are as follows Fig. 9 shown. Fig. 9 In the figure, obvious characteristic peaks can be seen in the curves before MO purification (shown by the black line) and before MB purification (shown by the green line). The curve after MO purification coincides with the curve after MB purification (shown by the blue line). In the purified condensed water, the characteristic absorption peaks of the two dyes disappear, indicating that there are almost no dye molecules in the condensed water, and the purification performance is significant.

[0068] In addition, after the solar evaporator prepared in this embodiment was irradiated with sunlight for 10 hours, the salt resistance and evaporation effect did not change significantly, which means that the solar evaporator prepared in this application can operate stably for a long time, thereby avoiding the problem of traditional solar evaporators having surface salt crystals precipitated during long-term operation and reducing their evaporation efficiency.

[0069] In summary, the present invention effectively overcomes the deficiencies in the prior art and has a high industrial utilization value. The above embodiments serve to illustrate the substantive content of the present invention, but do not limit the protection scope of the present invention. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a MXene / chitosan / glutaraldehyde porous material, characterized in that: The following steps are involved: (1) precooling a MXene / chitosan homogeneous dispersion, placing the precooled dispersion in a coolant for directional ice crystal growth, obtaining a MXene / chitosan frozen sample, and freeze-drying to obtain a MXene / chitosan porous material; (2) adding the MXene / chitosan porous material prepared in step (1) into the glutaraldehyde aqueous solution, allowing the MXene / chitosan porous material to stand until the MXene / chitosan porous material is fully soaked, then taking it out and absorbing it, immersing it in water, absorbing it and finally drying it to obtain the MXene / chitosan / glutaraldehyde porous material.

2. The preparation method according to claim 1, characterized in that: The mass fraction of glutaraldehyde in the glutaraldehyde aqueous solution in step (2) is 40wt% to 60wt%.

3. The preparation method according to claim 1, characterized in that: The MXene / chitosan homogeneous dispersion in step (1) is prepared by adding chitosan powder to a MXene dispersion, dissolving the powder, and then ultrasonically defoaming the dispersion. The concentration of chitosan in the MXene / chitosan homogeneous dispersion is 20 to 30 mg / mL.

4. The preparation method according to claim 3, characterized in that: The MXene dispersion is prepared by uniformly dispersing MXene powder in an acetic acid aqueous solution. The concentration of MXene in the MXene dispersion is 4 mg / mL, and the volume fraction of acetic acid in the acetic acid aqueous solution is 2%.

5. The preparation method according to claim 4, characterized in that: The MXene is Ti3C2, Ti3C2T x 、Ti2CT x 、Nb2CT x wherein T is one of -OH, -Cl, and -F, and x is the number of T.

6. The preparation method according to claim 3, characterized in that: The precooling time in step (1) is 0.5 to 1 h, and the precooling temperature is -5 to 5°C.

7. The preparation method according to claim 6, characterized in that: The coolant in step (1) is -40°C ethanol, and the ice crystal growth time is 10 to 15 minutes.

8. A MXene / chitosan / glutaraldehyde porous material prepared by the method according to any one of claims 1 to 7.

9. Use of the MXene / chitosan / glutaraldehyde porous material according to claim 8 in the preparation of a solar evaporator.

10. The use according to claim 9, characterized in that: The solar evaporator comprises an evaporation structure and a support structure, wherein the evaporation structure is made of MXene / chitosan / glutaraldehyde porous material.

Citation Information

Patent Citations

  • Preparation method and application of super-hydrophobic aerogel with both ultrafast oil adsorption capacity and high compression recovery performance

    CN115282888A

  • Janus double-layer aerogel as well as preparation method and application thereof

    CN115725112A